Sales System at Bencoolen Coffee and Resto Based on Wireless Local Area Network (WLAN) - Julda Julda; Khairil Khairil; Sapri Sapri (Jurnal Komputer, Informasi dan Teknologi, 2021)
The purpose of this research is to develop a system that has been running so far by designing and building a Local Area Network computer network on the sales system at Bencoolen Coffee. Sales system at Bencoolen Coffee And Resto is made using Visual Basic .Net programming language and SQL Server 2008r2 database. This Sales System is based on Wireless Local Area Network with 4 access rights to use the application, namely administrator, cashier, chef, and consumer. With this sales system, it can help Bencoolen Coffe And Resto in managing food and beverage data, as well as daily sales that have been integrated into one unit. The sales system at Bencoolen Coffee And Resto is implemented with 5 laptops connected to 1 local network where 1 laptop is used as a server, 1 laptop is used as an administrator, 1 laptop is used as a chef, 1 laptop is used as a cashier, and 1 laptop is used as a consumer, which has different functions. vary. Based on the results of the tests that have been carried out, the functionality of the Sales system at Bencoolen Coffee And Resto runs as expected, and the system is able to carry out data processing within the scope of the Bencoolen Coffee And Resto network.